Clinical staging for youth at‐risk for serious mental illness: A longitudinal perspective. Issue 5 (9th October 2020) - Addington, Jean; Liu, Lu; Farris, Megan S.; Goldstein, Benjamin I.; Wang, Jian Li; Kennedy, Sidney H.; Bray, Signe; Lebel, Catherine; MacQueen, Glenda
Abstract: Objective: The objective of this study was to identify a sample of youth in distinct stages of risk for the development of a serious mental illness (SMI) according to a published clinical staging model and to follow this sample longitudinally to determine clinical changes over time. This article reports the 6‐ and 12‐month follow‐up of the cohort. Methods: This study recruited 243 youth, ages 12 to 25. The sample included (a) 42 healthy controls, (b) 41 nonhelpseeking individuals with no mental illness but some risk of SMI, for example, having a first‐degree relative with an SMI (stage 0), (c) 53 youth experiencing distress and mild symptoms of anxiety or depression (stage 1a), and (d) 107 youth with attenuated symptoms of SMIs such as bipolar disorder or psychosis (stage 1b). Participants completed a range of measures assessing depression, anxiety, mania, suicide ideation, attenuated psychotic symptoms, negative symptoms, anhedonia and beliefs about oneself at baseline, 6‐ and 12‐months. Results: There were few changes for healthy controls and stage 0 participants, although approximately 7% did move to a symptomatic stage within 12‐months. Of stage 1a participants, 50% remained symptomatic, with 7.5% moving to stage 1b or developing a SMI. Approximately 9% of stage 1byouth developed a SMI within 12‐months and approximately one‐third had remission of symptoms during the follow‐up. Conclusions: Results suggest that the implementation of a transdiagnostic staging model may be useful in youth mental health and support consideration of clinical stage‐based treatment for youth with early features of risk.